A grain boundary interaction model for microstructurally short fatigue cracks. (August 2018) - Panwar, S.; Adams, J.F.; Allison, J.E.; Jones, J.W.; Sundararaghavan, V.
Highlights: A new crack-grain boundary interaction model is shown for crack retardation/arrest. An unequal coupling of the tilt and twist misorientations is presented. Tests on WE43 samples show the need to combine various interaction parameters. Our model predicts basal crack retardation and arrest at various grain boundaries. Abstract: In this paper, we present a phenomenological model for simulating the effect of a grain boundary on crack growth along crystallographic planes. This model combines various geometrical features of the interaction between the crack plane and the grain boundary plane. The tilt and twist misorientations, calculated at a grain boundary, between a crack plane and a favorable plane in the next grain are incorporated into this model, as are the Schmid factor of the next grain and a critical crack transmission stress. A model calibration procedure is demonstrated based on experimental short fatigue crack growth data measured in a high performance wrought magnesium alloy. The proposed combined GB interaction model is shown to accurately predict the short fatigue crack growth retardation and arrest at grain boundaries in this alloy.